Extension of multi-commodity closed-loop supply chain network design by aggregate production planning - Leena Steinke; Kathrin Fischer (Logistics Research, 2016)
In this work the influence of production and capacity planning on decisions regarding facility location, distribution quantities and component remanufacturing (and vice versa) in a closed-loop supply chain network (CLSCN) with multiple make-to-order products is studied. A mathematical model, the facility location, capacity and aggregate production planning with remanufacturing (FLCAPPR) model, for designing the CLSCN, for planning capacities at the facilities and for structuring the production and distribution system of the network cost-optimally, is formulated. It consists of a facility location model with component remanufacturing over multiple time periods, which is extended by capacity and production planning on an aggregate level. The problem is solved for an example set of data which is based on previous CLSC research in the copier industry. In a numerical study the effect of the extended planning approach on the decision to process returned products is determined. Furthermore, the FLCAPPR model is solved for different returned product quantities and numbers of periods in the planning horizon to study the influence on the network design and on the procuring, production and distribution quantities. It turns out that decisions regarding the locations of and the capacity equipment at facilities and decisions regarding the production and distribution system are interdependent; therefore, they have to be managed jointly. Furthermore, it is shown that the decision to process returned products and use remanufactured components in the production does depend not only on the costs, but also on the quantity of returned products and the length of the planning horizon.
Keywords: 650; Closed-loop supply chain management; Network design; Remanufacturing; Reverse logistics; Aggregate production planning; Capacity planning